THE FAMILY ENVIRONMENT IN THE CHILD’S LEARNING PROCESS - Raquel Rosin Soares , Ana (Revista Gênero e Interdisciplinaridade, 2022)
When thinking about learning, the formal way is immediately visualized, the one that takes place at school, but it happens before that, from the birth of the child, in the interaction with their peers. The article shows, from bibliographic research, that it is necessary, for a healthy development of the child, an active participation of the family, taking responsibility for learning by becoming a mediator. And that this family environment will make all the difference in the life of this being in formation. Regardless of the family constitution to which she belongs, it is in this sphere that affective, physical and cognitive stimuli will be necessary for satisfactory learning to take place. As well, it is observed that the lack of them causes damage to the child’s learning.